THE EFFECT OF PREVENTION EFFORTS ON STUNTING INCIDENTS IN CHILDREN - IGA Mirah Widhisastri; Yeyen Putriana; Sisca Amelia Roswati Dewi (JOURNAL of HEALTH SCIENCE REVIEW, 2024)
Stunting is a condition of growth failure in toddlers due to chronic malnutrition and repeated infections, especially during the first 1,000 days of life, characterized by height that is not appropriate for their age. Stunting has a serious impact on the quality of life of toddlers in the future, so it is important to prevent it. The design of this research is an analytical survey with a case-control approach, aimed at determining the impact of preventive measures on the incidence of stunting in toddlers. The respondents of this study were 44 people, selected using the systematic random sampling technique. The instruments used were questionnaires and the Maternal and Child Health book. The data analysis used is Chi-Square. The results of this study indicate that there is an influence of the history of consuming Iron Supplement Tablets (p-value 0.000, OR 28.98), Early Initiation of Breastfeeding (p-value 0.005, OR 17.5), Exclusive Breastfeeding (p-value 0.011, OR 7.6), Complementary Feeding (p-value 0.012, OR 14.5), and Immunization (p-value 0.021, OR 12.0) on the incidence of stunting in toddlers. The conclusion of this study is that there is a significant impact of preventive measures on the incidence of stunting in toddlers. Suggestions for health workers and health cadres to be more proactive in implementing stunting prevention efforts to reduce the incidence of stunting in toddlers